Contemplative discernment in a digital age: Ignatian pedagogy and the promise of AI-mediated education - Rukiyanto, Bernardus Agus (Proceedings of International Conference on Research in Education, 2025)
This article investigates how Ignatian Pedagogy can inform and transform the use of artificial intelligence (AI) in education, with the aim of promoting human dignity, ethical discernment, and ecological sustainability. The research objectives are threefold: (1) to explore the compatibility between the Ignatian Pedagogical Paradigm (IPP) and AI-mediated learning environments; (2) to identify pedagogical risks and ethical concerns arising from AI integration; and (3) to propose a model that aligns AI-supported practices with Ignatian educational values. The study employs a qualitative, conceptual research method through critical analysis of literature on Ignatian pedagogy, AI ethics, and educational innovation, complemented by contextual reflection based on the Indonesian educational landscape and the mission of Sanata Dharma University. The findings suggest that while AI offers pedagogical enhancements, it also requires frameworks that preserve relationality, reflection, and human formation. The article proposes a hybrid Ignatian-AI model structured around the IPP’s five dimensions—context, experience, reflection, action, and evaluation—each critically examined for its AI-compatible applications. The article concludes that Jesuit education can lead the way in developing ethically grounded, spiritually aware, and contextually sensitive approaches to AI-mediated education.
Keywords: artificial intelligence; ethical formation; Ignatian pedagogy; Jesuit education; reflective discernment